System Design Spare part Supply of the Blue Bird taxi pool Ciputat Using Visual Basic 6.0 - author author (Jurnal Sistem Informasi, 2006)
Once you know the things that related to Warehouse Stock Spare part in pool Ciputat Blue Bird taxi, the author provides only a guideline for discussing the procurement process and management of spare part in activities out-entry of spare parts. The aim of this study is to create an application program using Microsoft Access which can be: obtaining information and location of spare part in place, eliminate or reduce the reporting errors, Help the warehouse to find out how many spare parts are still in storage, Easy in the exit-entry transactions spare parts.